2020
DOI: 10.18203/2394-6040.ijcmph20203399
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of internet addiction amongst arts, commerce, engineering and medical students

Abstract: Background: With the advancement of technology across the world web and information have been interlinked. Internet is one of the channels for communication at a large platform just with a click and scrolling by fingertip. It is an impulsive disorder, which does not involve use of an intoxicating drug. When need get converted to demand we get addicted. Addiction causes depression, anger, loneliness and other medical problems too. Considering its variable use among different professionals, present study has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 15 publications
1
5
2
Order By: Relevance
“…These findings were in contrary to the results of the study done in Tanzania by Mboya et al, as they found that males were Internet addicts more than females (Mboya et al 2020 ) and also in contrary with Soni et al’s findings from their study in India as they found that prevalence of Internet addiction among medical students was more among males than females (Soni et al 2020 ).…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…These findings were in contrary to the results of the study done in Tanzania by Mboya et al, as they found that males were Internet addicts more than females (Mboya et al 2020 ) and also in contrary with Soni et al’s findings from their study in India as they found that prevalence of Internet addiction among medical students was more among males than females (Soni et al 2020 ).…”
Section: Discussioncontrasting
confidence: 72%
“…Regarding non-medical students; the present study also found that female students were more addicted to the Internet than male ones. This is in contrary with Soni et al’s results in their study on arts, commerce, and engineering students as they found that male students in these 3 colleges were addicted to the Internet more than female students (Soni et al 2020 ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These ndings were in contrary to results of study done in Tanzania by Mboya et al, as they found that males were internet addicts more than females (Mboya et al 2020) and also in contrary with Soni et al ndings from their study in Raipur, India as they found that prevalence of internet addiction among medical students was more among males tan females (22.5% of males were moderate internet addicts compared to only 7.5% of females while 2.5% of males were severe addicts and non of females were severe addicts) (Soni et al 2020). Also, our ndings were different from Srijampana et al, results as they found that males and females were equally suffered from internet without any difference (Srijampana et al 2014).…”
Section: Discussionmentioning
confidence: 80%
“…This is in contrary with Soni et al, ndings, as they found that medical students are less than students in faculty of engineering in internet addiction (2.5% of medical students and 12.5% of engineering students were severe internet addicts). However, they found that a similar percent of students in faculty of commerce (2.5%) and none of students in faculty of art were severe internet addicts (Soni et al 2020).…”
Section: Discussionmentioning
confidence: 96%